The Trojan Women by Jan Klata: – Tragedy on WW III(1) - Śmiechowicz, Olga (Sapiens ubique civis, 2023)
(1) I discussed this production in my monograph, Trojanki Jana Klaty (Kraków 2019) and in the article: Dramaturg pod Troją – praca nad tekstem „Trojanek” w reżyserii Jana Klaty. Meander 75 (2020) 219–230. In my paper I talk about my/our work on The Trojan Women directed by Jan Klata in Wybrzeże Theatre in Gdańsk (date of premiere 8th September 2018). I worked as the dramaturge of the play. The show was acclaimed by theatre critics as the best show of the season. It depicts all that Homer did not tell us in his Iliad: what the first morning after the seizure of Troy looked like. In our play, we preserve the poetic style and imagery of the ancient text written by Euripides. In our show we do not present white, classical marble sculpture-like characters: the show depicts the Greeks as cruel barbarians, who could not even make good use of their own victory. In my paper I describe our work on that show, familiarize the reader with our decisions and problems that we had found during our work.